Advances in aviation radiation mitigation demonstrated during the Gannon storm - Tobiska, W. K.; Hogan, B.; Didkovsky, L.; Judge, K.; Bailey, J.; Drumm, K.; Wahl, K.; Sosnov, A. (Frontiers in Astronomy and Space Sciences, 2025)
The validation of a strategy for aviation radiation hazard mitigation, in development for decades, has been completed using two commercial airline flights in 2024 and 2025. This study provides a historical review of the primary elements leading to that strategy, including the emergence of aviation radiation awareness and collaborative efforts by global aviation and radiological bodies to establish mitigation standards. The primary radiation sources, galactic cosmic rays (GCRs) and solar energetic particles (SEPs), and their mechanisms of impact on Earth’s atmosphere are summarized. The study highlights the biological effects of radiation exposure influenced by altitude, latitude, and geomagnetic conditions upon aircrew, frequent flyers, and commercial space travelers. It recognizes a recent Space Weather Advisory Group (SWAG) report that identifies the need for continuous monitoring and predictive models to ensure long-term occupational and public health safety. With this background, the validation of an as-low-as-reasonably-achievable (ALARA) strategy was accomplished using two UAL 990 flights on B777-200 aircraft between San Francisco and Paris. Each carried the same ARMAS FM7 radiation monitoring unit, with one flight during the extreme geomagnetic storm (Gannon storm) 10–11 May, 2024 and one flight during quiet geomagnetic conditions 8–9 June, 2025. The flights’ results validated the strategy during extreme space weather of applying operational controls for shielding to reduce dose. One approach is flying at lower magnetic latitudes to gain more Earth magnetic field shielding, and the other is flying lower altitudes to use atmosphere depth shielding. Both ALARA shielding methods are controllable in airline operations and air traffic management. These have now been validated with total dose measurements by ARMAS. This study shows the effectiveness of deviating flight paths to lower magnetic latitude routes and lower altitudes during major geomagnetic storms. Not only does this approach mitigate HF communication outages, but it also reduces risks from increased GNSS errors for take-off and landing navigation. Magnetic field shielding is a major risk reduction factor for radiation, communication, and navigation, while altitude shielding reduces radiation hazard risks.